Supplementary laboratory in digital circuit and logic design course for pre-service vocational teacher in Thailand - Chayratsami, Pornpimon (My University, 2013)
This paper provides an evaluation of a teaching method using a supplementary laboratory, that utilizes 3 types of laboratory setups to increase the understanding and hands-on skill in a digital circuit and logic design class for pre-service vocational teacher in Thailand. The laboratories include building a digital circuit using logic blocks, doing a computer simulation, and using a programmable logic device (PLD). The effectiveness of the teaching method is evaluated based on students' feedbacks, backgrounds, opinions, and scores. The tools, used in this research, are a set of lab sheets, a computer simulation program called 'Digital Works', and a portable equipment box. After two consecutive years of teaching and using the supplementary laboratory in the digital circuit and logic design class, the students have the same opinions that the laboratory helps them to understand the theories, they will be able to apply the knowledge to the related advance courses, and they agree that all 3 parts of the laboratory are necessary and encourage them to have more hands-on skill. In addition, students' scores show that the students have better grades in average by using the supplementary laboratory. © 2013 IEEE.
Keywords: Digital circuit and logic design; Laboratory; Pre-service vocational teacher; Teaching methodology